2005
DOI: 10.1097/01.sla.0000164177.95620.c1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Down-Regulation of 15-Lipoxygenase-1 Is Reversed by Celecoxib in Colorectal Cancer

Abstract: 15-LOX-1 gene expression is significantly reduced in both human colorectal adenomas and carcinomas and associated with decreased survival. Administration of celecoxib restores 15-LOX-1 protein expression and induces apoptosis. Down-regulation of 15-LOX-1 is an early event in the adenoma to carcinoma sequence, and reversal with celecoxib may represent one mechanism for chemoprevention of polyps or treatment of carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 17 publications
3
55
1
Order By: Relevance
“…NSAIDs induce 15-LOX-1 in association with apoptosis induction, even in systems involving non-COX-2-inhibiting NSAIDs and non-COX-2-expressing colorectal cancer cells (101). These NSAID/15-LOX-1 findings have been confirmed by two other groups in colorectal cancer (102,103) and have been extended to other cancers, including esophageal (104) and gastric (105) cancer. Our group has shown that interactions between 15-LOX-1 signaling and GATA-6, protein kinase G, histone deacetylase, and methyltransferase (which are upstream regulators) and PPAR-y and PPAR-g (which are downstream mediators) are COX-2-independent mechanisms involved in 15-LOX-1-induced apoptosis and anticarcinogenic activity (106)(107)(108)(109)(110)(111).…”
Section: Molecular Targeting and The Risk Of Cancer Preventionsupporting
confidence: 64%
“…NSAIDs induce 15-LOX-1 in association with apoptosis induction, even in systems involving non-COX-2-inhibiting NSAIDs and non-COX-2-expressing colorectal cancer cells (101). These NSAID/15-LOX-1 findings have been confirmed by two other groups in colorectal cancer (102,103) and have been extended to other cancers, including esophageal (104) and gastric (105) cancer. Our group has shown that interactions between 15-LOX-1 signaling and GATA-6, protein kinase G, histone deacetylase, and methyltransferase (which are upstream regulators) and PPAR-y and PPAR-g (which are downstream mediators) are COX-2-independent mechanisms involved in 15-LOX-1-induced apoptosis and anticarcinogenic activity (106)(107)(108)(109)(110)(111).…”
Section: Molecular Targeting and The Risk Of Cancer Preventionsupporting
confidence: 64%
“…15-LOX-1/-2 is downregulated in human colorectal tumors (118), and administration of 15-LOX-1 has shown anticarcinogenic effects (28). H. pylori induce 5-LOX-derived LT production in human gastric epithelial cells (GEC) contributing to the neutrophil infiltration characteristic of the inflammation associated with infection (104 1 O 2 is not a free radical, but has properties similar to ROS due to its electronic structure.…”
Section: Phoxmentioning
confidence: 99%
“…lymphomas, lung, prostate and cervix cancers [72,73] . In keeping with this, demethylation of DNA in some cell lines was shown to increase 15-LOX-1 expression in a study by Heslin et al [39] . However, in colon cancer cell lines, conflicting data have emerged, when 5-aza-2-deoxycytidine (5-aza-dc), a hypomethylating agent, was shown to increase15-LOX-1 expression in some publications [62] and failed to induce the same in others [63] .…”
Section: Dna Methyltransferase and Promoter Site Methylationmentioning
confidence: 73%
“…Yuri et al [38] have reported down-regulation of 15-LOX-1 in colorectal adenomas. Heslin et al [39] established a positive relationship between 15-LOX-1 expression and survival in stage IV (TNM staging) colorectal cancer patients. In separate studies, 13-S-HODE added to the growth medium was found to induce apoptosis in RKO (COX-2-positive), Caco-2 (COX-2-positive), DLD1 (COX-2-negative) and SW480 colorectal cancer cells [23,24,37,40] .…”
Section: Anti-carcinogenic Roles Of 15-lox-1 In Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation